Aflatoxin B1 contamination in porridge formulations for children and ingredients sourced from selected markets in Rwanda - Matabishi, M.; Mutua, Florence; Lindahl, Johanna F.; Hahirwa, I.; Umugwaneza, M.; Musafili, A.; Munyanshongore, C. (African Scholarly Science Communications Trust, 2024)
Providing safe and nutritious food for children globally is a challenge. In Rwanda, an initiative was introduced in 2018 to tackle chronic malnutrition by offering fortified porridge flour to economically disadvantaged families during critical periods. However, flour-based products in the sub-region have caused public health concerns following aflatoxin B1 (AFB1) contamination. This study analyzed the levels of AFB1 in 197 porridge formulations from health centers, and 248 samples of porridge ingredients from open markets in three districts of Rwanda. Samples were collected between June 2021 and December 2022 and analyzed using ultra-high-performance liquid chromatography. Of the 197 samples from health centers, 97.9 and 89.8% exceeded the European Union maximum limits for baby foods and foods for special medical purposes (0.1 µg/kg), and cereals and nuts (2 µg/kg), respectively with an average contamination level of 2.77 µg/kg (±0.98). Only four samples exceeded the East African Community maximum limits of 5 µg/kg for AFB1. Samples from open markets that exceeded the European Union and East African community limits of 0.1 µg/kg, 2 µg/kg, and 5 µg/kg ranged from 17 to 100%, 0 to 100%, and 0 to 100%, respectively. Site and processing significantly influenced levels of AFB1 contamination in open-market samples. The mean AFB1 levels were 17.85 µg/kg (±70.25) in Burera District, 36.04 µg/kg (±85.59) in Huye District, and 9.01 µg/kg (±18.49) in Nyarugenge District. The average AFB1 levels significantly varied between different products. Peanut samples showed higher contamination levels of 56.79 and 99.08 µg/kg for grain and flour, respectively. Flour samples in general had a higher mean of 51.65 µg/kg (±105.75), compared to grain samples, 16.5 µg/kg (±44). Thus, there are potential health risks associated with chronic exposure to AFB1 in children consuming flourbased foods from health centers and open markets. Interventions to mitigate AFB1 contamination and protect children should focus on food processing practices, implementing strict quality control measures, and raising awareness among stakeholders about the risks of AFB1 in flour-based products provided to children in Rwanda and similar settings.